2022
DOI: 10.1101/2022.10.01.510468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DELE1 oligomerization promotes integrated stress response activation

Abstract: Mitochondria are dynamic organelles that must continually adapt and respond to cellular stress. Recent studies demonstrated that mitochondrial stress can be relayed from mitochondria to the cytosol by the release of a C-terminal proteolytic fragment of DELE1 that binds to the eIF2α kinase HRI to initiate integrate stress response (ISR) signaling. Here, we report the cryo-electron microscopy structure of the active, C-terminal cleavage product of human DELE1 at ~3.8 Å resolution. Our structure reveals that DELE… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…1B). Additionally, the predicted truncated protein product (resulting from the predicted frameshift mutation p.Arg21GInfsTer19), if expressed, would lack part of the targeting sequence needed for mitochondrial localization and the tetratricopeptide repeat (TPR) domains required for HRI binding and downstream signaling (Yang et al , 2023).…”
Section: Resultsmentioning
confidence: 99%
“…1B). Additionally, the predicted truncated protein product (resulting from the predicted frameshift mutation p.Arg21GInfsTer19), if expressed, would lack part of the targeting sequence needed for mitochondrial localization and the tetratricopeptide repeat (TPR) domains required for HRI binding and downstream signaling (Yang et al , 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, we tested the ability of these compounds to activate a luciferase-based reporter of ATF4 translation (ATF4-FLuc) as an indicator of ISR activity in HEK293T cells ( Fig. S1A ) (Yang et al , 2022). We confirmed that thapsigargin (Tg), a SERCA inhibitor that activates the ER stress responsive PERK ISR kinase, robustly increases ATF4-FLuc activity ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…OMA1 -deficient HEK293T cells, DELE1 -deficient HEK293T cells, and HRI -deficient HEK293T cells were described previously (Guo et al ., 2020) and cultured at 37°C and 5% CO2 in DMEM (Corning-Cellgro) supplemented with 10% fetal bovine serum (FBS; Omega Scientific), 2 mM L-glutamine (GIBCO), 100 Units/mL penicillin, and 100 mg/mL streptomycin (GIBCO). HEK293T cells stably expressing ATF4-FLuc or ATF4-mAPPLE CRISPRi-depleted of HRI , GCN2 , PERK , or PKR were described previously (Guo et al ., 2020; Yang et al ., 2022) and cultured at 37°C and 5% CO2 in DMEM (Corning-Cellgro) supplemented with 10% fetal bovine serum (FBS; Omega Scientific), 2 mM L-glutamine (GIBCO), 100 Units/mL penicillin, and 100 mg/mL streptomycin (GIBCO). MEF mtGFP cells (kind gift from Peter Schultz, TSRI)(Wang et al , 2012) were cultured at 37°C and 5% CO2 in DMEM (Corning-Cellgro) supplemented with 10% fetal bovine serum (FBS; Omega Scientific), 2 mM L-glutamine (GIBCO), 100 Units/mL penicillin, and 100 mg/mL streptomycin (GIBCO).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether HRI forms coalescences in cells remains to be investigated. Recent structural findings have revealed that DELE1 organizes into an octamer capable of modulating HRI activity, raising the possibility that DELE1 multimers may template HRI multimerization to facilitate autophosphorylation (Yang et al, 2023).…”
Section: Spatial Organization Of Isr Components Within Cellsmentioning
confidence: 99%